2015
DOI: 10.1589/jpts.27.2667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of consecutive application of stretching, Schroth, and strengthening exercises on Cobb’s angle and the rib hump in an adult with idiopathic scoliosis

Abstract: [Purpose] To report the effects of consecutive application of stretching, Schroth, and strengthening exercises in an adult with idiopathic scoliosis. [Subject] A 26-year-old woman with idiopathic scoliosis, Cobb’s angle of 20.51°, and back pain. [Methods] The exercise program consisted of 3 sessions: 10 minutes of stretching exercises, 20 minutes of Schroth exercises, and 10 minutes of strengthening exercises. This program was implemented 3 times a week, for 8 weeks. [Results] The thoracic Cobb’s angle decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 16 publications
(20 reference statements)
3
21
0
1
Order By: Relevance
“…Previous studies have also reported significant decreases in pain and Cobb’s angle and increased quality of life8,9,10,11, 13 ) . Thus, the Schroth method allows patients to regain normal posture of elongation, de-rotation, and de-flexion of the spine by continuous feedback of visual information8,9,10,11, 13 ) . Therefore, the Schroth method decreases pain and Cobb’s angle by inhibiting compensation and restoring appearance.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Previous studies have also reported significant decreases in pain and Cobb’s angle and increased quality of life8,9,10,11, 13 ) . Thus, the Schroth method allows patients to regain normal posture of elongation, de-rotation, and de-flexion of the spine by continuous feedback of visual information8,9,10,11, 13 ) . Therefore, the Schroth method decreases pain and Cobb’s angle by inhibiting compensation and restoring appearance.…”
Section: Discussionmentioning
confidence: 78%
“…The Schroth method helps correct posture depending on the scoliosis type10, 11 ) . In addition, a therapist educated in the memory of corrected posture recognizes abnormal during activities of daily living8, 9, 12, 13 ) . Patients with idiopathic scoliosis must consider the of changed appearance after treatment and adjustment of Cobb’s angle8 ) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The objective of exercise is to reduce symptoms and improve functional capacity and quality of life. [10][11][12][13][14][15] Although braces are mainly used in these patients, the isolated effects of corrective, therapeutic exercise on AIS patients are not clear; 1 actually, the Scientific Society on Scoliosis Orthopaedic Rehabilitation and Treatment (SOSORT) 16 has shown that the evidence of conservative management in these patients is scarce.…”
Section: Introductionmentioning
confidence: 99%